Effects of anti-inflammatory drugs on fever and neutrophilia induced by Clostridium difficile toxin B - R. A. Cardoso; A. A. Melo Filho; M. C. C. Melo; D. M. Lyerly; T. D. Wilkins; A. A. M. Lima; R. A. Ribeiro; G. E. P. Souza (Mediators of Inflammation)
This study investigated the ability of Clostridium difficile toxin B, isolated from the VPI 10463 strain, to induce fever and neutrophilia in rats. Intravenous injection of toxin B (0.005–0.5 μg/kg) evoked a dose-dependent increase in body temperature. The febrile response to 0.5 μg/kg of the toxin started in 2.5 h, peaked at 5 h, and subsided fully within 24 h. Toxin B also induced a dosedependent neutrophilia. Pretreatment with indomethacin (2 mg/kg, i.p.) did not affect the neutrophilia induced by toxin B, but significantly reduced the febrile response measured 4 to 8 h after toxin B injection. Dexamethasone (0.5 mg/ kg) also markedly diminished the febrile response induced by toxin B. These results show that Clostridium difficile toxin B induced a febrile response susceptible to inhibition by dexamethasone and indomethacin. Furthermore, they suggest that prostaglandins are not involved in the neutrophilia caused by this toxin.